# Toán Lớp 6: 2(x – 5) – 3(x + 7) = 14 3(x – 4) – (8 – x) = 12 x – 12 – 25) = -8 175 – 5(x + 3) = 85

Toán Lớp 6: 2(x – 5) – 3(x + 7) = 14
3(x – 4) – (8 – x) = 12
x – 12 – 25) = -8
175 – 5(x + 3) = 85

TRẢ LỜI

1. tuyethutanhthu
2 ( x – 5 ) – 3 ( x + 7 ) = 14
⇔ 2x – 10 – 3x – 21 = 14
⇔ – x – 31 = 14
⇔ – x = 14 + 31
⇔ – x = 45
⇔ x = – 45
Vậy x = – 45
———————————–
3 ( x – 4 ) – ( 8 – x ) = 12
⇔ 3x – 12 – 8 + x = 12
⇔ 4x – 20 = 12
⇔ 4x = 12 + 20
⇔ 4x = 32
⇔ x = 8
Vậy x = 8
—————————————–
x – ( 12 – 25 ) = – 8
⇔ x – 12 + 25 = – 8
⇔ x + 13 = – 8
⇔ x = – 8 – 13
⇔ x = – 21
Vậy x = – 21
————————————
175 – 5 ( x + 3 ) = 85
⇔ 175 – 5x – 15 = 85
⇔ 160 – 5x = 85
⇔ – 5x = 85 – 160
⇔ – 5x = – 75
⇔ x = ( – 75 ) : ( – 5 )
⇔ x = 15
Vậy x = 15

Trả lời
2. maingocquynhnhu2k1
2(x – 5) – 3(x + 7) = 14
<=>2x-10-3x-21=14
<=>2x-3x=14+10+21
<=>-x=45
<=>x=-45
Vậy x=-45

3(x – 4) – (8 – x) = 12
<=>3x-12-8+x=12
<=>3x+x=12+12+8
<=>4x=32
<=>x=32:4=8
Vậy x=8

x-(12-15)=-8
<=>x-12+15=-8
<=>x+3=8
<=>x=8-3=5
Vậy x=5

175 – 5(x + 3) = 85
<=>175-5x-15=85
<=>-5x=85+15-175
<=>-5x=-75
<=>x=15
Vậy x=15

Trả lời